Healing Spaces: Emotional Architecture Applied to Borderline Treatment - VALDIVIA ORTIZ, LEONARDO JOEL; GUTIÉRREZ ROJAS, MAURENAR KRUS; RODRÍGUEZ CASTAÑEDA, YESSENIA NATHALÍ (LACCEI, 2025)
The article highlights the increasing global prevalence of Borderline Personality Disorder (Borderline) in mental health, focusing on the specific situation in the region of Lambayeque, Perú, and notes the scarcity of specialized centers. In addition, research on emotional architecture is addressed, exploring the capacity of architectural design to impact emotions in physical environments. The methodology used to evaluate the theory of Emotional Architecture design criteria involves the analysis of meanings, conceptualization through representative graphics, and the derivation of specific theories from previous research. The design criteria, comprising the use of neutral colors, the arrangement of free spaces, and the manipulation of light and shadow, have been evaluated according to two guidelines, both of which yielded highly positive results, reinforcing the validity of the research, which aims to provide carefully considered models for improving environments for health.